Gerakan Sehat Sejak Dini Melalui Edukasi Jajanan Sehat pada Anak Usia Dini di TK Tunas Islam - Dwi Yati; Latifah Susilowati; Yanuar Primanda (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Unhealthy snack consumption may expose young children to excessive sugar, salt, fat, microbial contamination, and prohibited food additives. This community service activity aimed to improve children's understanding of healthy and unhealthy snacks at TK Tunas Islam, Kasihan, Bantul. The activity involved 75 children from playgroup and kindergarten classes and was conducted in June 2025. The program consisted of an initial assessment using simple pictorial questions, health education through short explanations, storytelling, visual presentations, posters, and small-group discussion, followed by a final assessment using the same ten questions. All participants attended the activity. Descriptive observations showed that, before education, many children had difficulty identifying safe snacks, the consequences of unhealthy snacks, and appropriate handwashing practices. After the session, more children were able to distinguish healthy from unhealthy snacks and respond correctly to the evaluation questions. Age-appropriate stories, pictures, and interactive discussion encouraged active participation and maintained children's attention. Participatory, visually supported education is feasible for introducing healthy snack choices in early childhood settings. Regular reinforcement by teachers and parents, along with standardized follow-up evaluation, is recommended to support sustainable healthy eating habits.